Host PDZ‐containing proteins targeted by SARS‐CoV‐2. (1st May 2021) - Caillet‐Saguy, Célia; Durbesson, Fabien; Rezelj, Veronica V.; Gogl, Gergö; Tran, Quang Dinh; Twizere, Jean‐Claude; Vignuzzi, Marco; Vincentelli, Renaud; Wolff, Nicolas
Abstract : Small linear motifs targeting protein interacting domains called PSD‐95/Dlg/ZO‐1 (PDZ) have been identified at the C terminus of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) proteins E, 3a, and N. Using a high‐throughput approach of affinity‐profiling against the full human PDZome, we identified sixteen human PDZ binders of SARS‐CoV‐2 proteins E, 3A, and N showing significant interactions with dissociation constants values ranging from 3 to 82 μm . Six of them (TJP1, PTPN13, HTRA1, PARD3, MLLT4, LNX2) are also recognized by SARS‐CoV while three (NHERF1, MAST2, RADIL) are specific to SARS‐CoV‐2 E protein. Most of these SARS‐CoV‐2 protein partners are involved in cellular junctions/polarity and could be also linked to evasion mechanisms of the immune responses during viral infection. Among the binders of the SARS‐CoV‐2 proteins E, 3a, or N, seven significantly affect viral replication under knock down gene expression in infected cells. This PDZ profiling identifying human proteins potentially targeted by SARS‐CoV‐2 can help to understand the multifactorial severity of COVID19 and to conceive effective anti‐coronaviral agents for therapeutic purposes. Abstract : The E, 3a, and N proteins of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) carry a PSD‐95/Dlg/ZO‐1 (PDZ)‐binding motif allowing interaction with PDZ‐containing proteins in infected cells. A high‐throughput approach of affinity‐profiling against the full human PDZome identified 16 human PDZ binders of SARS‐CoV‐2 proteins, out of which seven significantly affect viral replication under knock down gene expression in infected cells. Most of them are involved in cellular junctions/polarity.